2017
DOI: 10.1002/ijc.31169
|View full text |Cite
|
Sign up to set email alerts
|

ARHGEF19 interacts with BRAF to activate MAPK signaling during the tumorigenesis of non‐small cell lung cancer

Abstract: Rho guanine nucleotide exchange factors (RhoGEFs) are proteins that activate Rho GTPases in response to extracellular stimuli and regulate various biologic processes. ARHGEF19, one of RhoGEFs, was reported to activate RhoA in the Wnt-PCP pathway controlling convergent extension in Xenopus gastrulation. The goal of our study was to identify the role and molecular mechanisms of ARHGEF19 in the tumorigenesis of non-small cell lung cancer (NSCLC). ARHGEF19 expression was significantly elevated in NSCLC tissues, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 50 publications
(113 reference statements)
1
24
0
Order By: Relevance
“…Cell invasion was tested using a Transwell assay 46 , 47 . Briefly, 2 × 10 5 cells in 200 μL serum-free or complete medium were seeded into the Boyden chamber with Matrigel (8-μm pore; BD Falcon, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Cell invasion was tested using a Transwell assay 46 , 47 . Briefly, 2 × 10 5 cells in 200 μL serum-free or complete medium were seeded into the Boyden chamber with Matrigel (8-μm pore; BD Falcon, USA).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, various cancer tissues and cell lines show elevated levels of Ephexin2, which results in the increased activity of RhoA causing higher cancer proliferation, migration, and invasion. The downregulated levels of Ephexin2 by miR-503 have an inhibitory effect on cancer metastasis in hepatocellular carcinoma model and miR-29b, which downregulates the levels of Ephexin2, is decreased in non-small cell lung cancer (NSCLC) [39,40]. Interestingly, the roles of Ephexin2 during pronephric tubulogenesis and in the cancer are relevant to the high expression levels of Ephexin2 in the kidney, as well as the liver and lung.…”
Section: Ephexin Familymentioning
confidence: 99%
“…For example, it has been reported that they regulate angiogenesis [34], efferocytosis, a type of phagocytosis to clear apoptotic cells in the body [35,36,37], and vascular muscle contractility [18]. Moreover, aberrant expression or function of Ephexins are related to various types of cancer [38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53]. Thus, the roles of Ephexins are not limited to the nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…Stable cell lines with overexpressing or silenced LAMC2 were established according to the methods described previously. 31,32 Briefly, LAMC2 cDNA was cloned into the pCDH-EF1-CMV-MCS-T2A-Puro vector (System Biosciences, Palo Alto, CA, USA), and LAMC2 shRNAs (Table S3) were inserted into the pLko.1 vector (Sigma-Aldrich Co., St. Louis, MO, USA). Recombinant lentiviruses were packaged in 293T cells and used to construct the stable cell lines.…”
Section: Cell Lines and Establishment Of Stable Cell Linesmentioning
confidence: 99%
“…Male BALB/c nude mice (4-5 weeks old; SLRC Laboratory Animals, Shanghai, China) were used to generate an inguinal LN metastasis model, as described previously. 31 Two million cells were injected into the foot pads of the mice (n=10/group). The mice were killed after 10~12 weeks, and inguinal LNs were examined.…”
Section: Animal Experimentsmentioning
confidence: 99%